ASSESSMENT OF F HOUSING AVAILABILITY FOR THE POPULATION IN DNIPROPETROVSK REGION - Bozhanova, V. Yu.; Razumova, V. A. (Science and Transport Progress, 2009)
In the article the main modern progress of the housing market trends are considered. The calculations of coefficient of housing price to income ratio for the population of Dnipropetrovs’k region are produced. The results of these calculations are analyzed too.